Enigmatic Sulawesi: The tectonic collage - Baillie, Peter; Decker, John (Berita Sedimentologi, 2022)
Sulawesi has a complex tectonic history that is affected by major plate re-organisations during the Cenozoic resulting in an extension-dominated setting in an overall setting of convergence of the Indo-Australian, Pacific and Philippine Sea, and Eurasian plates. It is a complex collage of disparate tectonic terranes brought into juxtaposition by a variety of tectonic processes which have occurred at very fast rates. The island is subject to a variety of geohazards related to earthquake and volcanic activity.